ROLE OF MEDICAL STAFF IN THE ONCOLOGY DEPARTMENT IN THE PSYCHOLOGICAL CARE OF CHILDREN AND ADOLESCENTS WITH CANCER - Guellil Mohammed Réda; Ainad Tabet Ismail (International Journal of Innovative Technologies in Social Science, 2025)
This study aimed to identify Role of medical staff in the oncology department in the psychological care of children and adolescents with cancer, as well as to know the position taken by medicine in the treatment of psychological aspects of cancer in children. This is an exploratory qualitative study and was conducted at the Pediatric Oncology Department of Oran. Clinical interviews were used, because it is a methodological tool that allows direct and personal contact with a source of information from a versatile conversation to obtain clear answers to our question. The observation grid was also used as a research tool which lists a set of criteria. The results of this study confirmed the validity of the previously proposed hypothesis and indicate that the participation of medical staff in the psychological support of children with cancer during treatment is crucial for the quality of care provided to these children.